TINGKAT KEMATANGAN GONAD IKAN KERLING JANTAN, Tor tambroides, (Cyprinidae) YANG TERTANGKAP DI DAERAH ALIRAN SUNGAI JAMBAK KABUPATEN ACEH BARAT: PENDEKATAN HISTOLOGI - Afrizal Hendri; Baihaqi Baihaqi (Universitas Teuku Umar, 2015)
The study about gonado somatic level of fresh water is database for controlling breeding and conservation in the future. Some asessment can conducted to observing gonado somatic index is with plasma levels (hormone), gonado somatic index dan histology. Tor tambroides (local name is kerling) is one of fresh water species in Aceh. However, exploitation of fish (Tor tambroides) and degradation of river habitat is endanger for this species. This study aims to knowing profile gonado somatic of Tor tambroides especially male fish with histolgy approach. Sampling of fish was conducted during 6 months i.e. July – December. For fish catching, this research was using cast net with mesh size 1 inch and 2 inch. Explorative survey was used for sampling strategy. Histology analysis was conducted at histology laboratorium (Balai Budidaya Air Payau Ujong Batee, Aceh Province). Result show that development fish gonado of Tor tambroides stated with spermatogonia cell, spermatosit primer, spermatosit secondary dan spermatid dan this result is found in every months. Nevertheless, dominant propostion value is spematogenesis with value 55%. Base on the research is known Tor tambroides (male fish) entering spawning session on July.